The effect of exercise therapy and range of motion (rom) on chronic ankle instability (cai) in pelatda pon xx athletes dki jakarta province - Linda Birawati; Junaidi; Ramdan Pelana; Fatah Nurdin (Gladi : Jurnal Ilmu Keolahragaan, 2022)
The purpose of this study is to determine the effect of exercise therapy methods and athlete's ROM on chronic ankle instability (CAI). The research method is an experiment with a treatment by level 2x2 design. The population of the athletes of Pelatda PON XX DKI Jakarta Province who experience chronic ankle sprain is 74 athletes. The number of samples from each level are: group (B1) is 27% of 74 = 19.98 (20) sample and group (B2) is 27% of 74 = 19.98 (20) sample. The research sample was 40 people. Hypothesis testing using the Tukey test. Based on the research results, it can be concluded: 1) there is a significant difference between the A1 and A2 methods on Y. Judging from Fo = 54.269 sig. 0.00<0.05. 2) There is a significant interaction effect between A and B on Y. Judging from Fo = 54.269 sig. 0.00<0.05. 3) there is a significant difference in Y using exercise therapy A1 and A2 in group B1. This is evidenced by the value of sig. 0.00<0.05. 4) there is a significant difference in Y results using exercise therapy A1 and A2 in group B2. It is proven by the value of sig. 0.00<0.05.